Sensing the sacred - Gerety, Finnian M. M. (2021)
"On Sensing the Sacred, we delve into the past and present of religion, politics, and society in South Asia, highlighting the latest academic research through conversations with leading scholars. A new podcast from the Center for Contemporary South Asia at the Watson Institute at Brown University, hosted by Finnian M.M. Gerety"